Avaliação de parâmetros métricos oculares pela fotografia digital da face: uso do diâmetro da íris como unidade de referência - Miot, Hélio Amante [UNESP]; Pivotto, Daniel Rosito; Jorge, Edson Nacib [UNESP]; Ferreira da Silva Mazeto, Glaucia Maria (Conselho Brasileiro de Oftalmologia, 2008)
Purpose: To evaluate reproducibility and precision of ocular measurements by digital photograph analysis, in addition to the transformation of the measures according to the individual iris diameter as an oculometric reference. Methods: Twenty-four eyes have been digitally photographed in a standardized way at two distances. Two researchers have analyzed these printed images using a caliper and these digital forms by ImageJ 1.37 (TM). Several external ocular parameters were estimated (mm and as iris diameter) and methods of measurement compared regarding their precision, agreement and correlation. Results: Caliper and digital analysis of oculometric measures provided significant agreement and correlation, nevertheless the precision of digital measures was higher. The estimates of numeric transformation from oculometric measures according to individual iris diameter resulted in great correlation to caliper measures and high agreement when compared to different distances of taking the photographs. Conclusions: Facial digital photographs allowed oculometric precise and reproducible estimates, endorsing clinical research usefulness. Using iris diameter as individual oculometric reference disclosed high reproducibility when facial photographs were taken at different distances.
Evaluation of oculometric parameters by facial digital photography: use of iris diameter as a reference
Keywords: Eye; Photography; Biometry; Iris; Measures; Image processing; computer-assisted; Eyelids